Prayers in stone : Greek architectural sculpture ca. 600-100 B.C.E. - Ridgway, Brunilde Sismondo, 1929- (Sather classical lectures ;, 1999)
This book is a comprehensive treatment of the significance of Greek architectural sculpture. The meaning of architectural sculpture is essential to our understanding of ancient Greek culture. The embellishment of buildings was common for the ancient Greeks, and often provocative. Some ornamental sculpture was placed where, when the building was finished, no mortal eye could view it. And unlike much architectural ornamentation of other cultures, Greek sculpture was often integral to the building, not just as decoration, and could not be removed without affecting the integrity of the building structure. The author provides a highly informative tour of many dimensions of Greek public buildings--especially temples, tombs, and treasuries.